Effect of lemongrass aromatherapy on insomnia severity among adult smokers: A quasi-experimental study - Kumboyono Kumboyono; Yati Sri Hayati; Mayu Rahmayanti; Titin Andri Wihastuti (Jurnal Keperawatan, 2026)
Introduction: Smoking is associated with a higher prevalence of insomnia and anxiety, which contributes to reduced sleep quality among adult smokers. Lemongrass aromatherapy has shown potential benefits in modulating sleep patterns and reducing anxiety symptoms.Objectives: This study aimed to investigate the effect of lemongrass aromatherapy on the severity of insomnia among smokers.Methods: A quasi-experimental pretest-posttest control group design was used with 50 adult smokers in each group selected through purposive sampling. Participants were divided into an intervention group that received lemongrass essential oil aromatherapy and a control group that received standard care. Insomnia Severity Index (ISI), GAD-7 for anxiety, and Fagerström Test for Nicotine Dependence (FTND) were used for data collection. Data were analysed using an independent t-test and a paired t-test.Results: The intervention group showed a significant reduction in insomnia scores (p-value < 0.01), whereas the control group showed no significant change. The improvement was more prominent among participants with moderate nicotine dependence and baseline anxiety symptoms. Given the applied community setting, the findings are subject to limitations related to the quasi-experimental design and unmeasured lifestyle factors, which should be considered when interpreting the results. Conclusions: Lemongrass aromatherapy is effective in reducing insomnia symptoms among smokers and may serve as a complementary therapy in community nursing care. The integration of aromatherapy into non-pharmacological nursing interventions is recommended to improve sleep quality.